Summa Theologica, Part III (Tertia Pars) : From the Complete American Edition - Thomas, Aquinas, Saint, 1225?-1274 (Salt Lake City, UT : Project Gutenberg, 2006)
"Summa Theologica, Part III (Tertia Pars)" by Saint Thomas Aquinas is a theological work written in the 13th century. This section focuses on Christ as humanity's path to God and the sacraments, though Aquinas left it incomplete. Using his distinctive question-and-answer method, he presents Christian doctrine through careful reasoning, addressing objections and citing sources from biblical, philosophical, and patristic traditions. This unfinished masterwork remains essential reading for Catholic theology students and continues influencing Western religious thought centuries later. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Summa_Theologica
Release date is 2006-11-28
Produced by Sandra K. Perry, with corrections and supplementation by David McClamrock
Keywords: Theology, Doctrinal -- Early works to 1800; Catholic Church -- Doctrines -- Early works to 1800; God -- Omnipresence -- Early works to 1800; God -- Attributes -- Early works to 1800